Characterisation of tri-ruthenium dihydride complexes through the computation of NMR parameters. - Al-Ibadi, M; Duckett, S; McGrady, J (2012)
Density functional theory has been used to provide atomic-level detail on the structures of metal hydride intermediates that have previously been proposed in the hydrogenation of phenylacetylene using Ru(3)(CO)(10)(PPh(3))(2). Based on a comparison of energetic data along with computed chemical shifts and coupling constants, we suggest that the detected species share a Ru(3)(μ-H)(μ-H) motif, with two distinct bridging hydride sites, rather than the terminal hydride proposed previously. The work illustrates how theory can be used as a complement to spectroscopy to enhance the accuracy of deductions, and to provide a basis for future rational design of second generation catalysts.